ANALISIS MINAT MENABUNG NASABAH DI BANK BCA SYARIAH CABANG SIDOARJO - Nafisa Rismayanti; Sugeng Hariadi; Mintarti Ariani (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2019)
The research was distributed by certain important factors to decide to save or invest. Clients also pay attention to service and savings products offered by the bank so that the customer would like to use it. Clients always want products that canmeet their needs, and asked the bank to provide the best service. Those factors are one of the things that affects the interests and needs of the behavior of customers. The purpose of this research is to know the influence of the quality of service, product quality, and profit sharing the results against the interest of saving the customer at BCA Bank Syariah in Sidoarjo. This research is quantitative descriptive research with survey method. The number of samples as many as 100 respondents, this research instrument in the form of an online questionnaire. Test instruments, test the classical assumptions, and test data analysis in this research using SPSS 20.00. The results of this study showed that the quality of service (????????), quality savings products (????????), and profit sharing (????????) jointly have a significant influence on relations and against the interest of saving the customer (Y) with the value F of 106.989 with the value significance of determination coefficients and 0.000 (????????) worth 0.763 (76.3%).